Association between body mass index and oesophageal cancer mortality: a pooled analysis of prospective cohort studies with >800 000 individuals in the Asia Cohort Consortium. (1st March 2022) - Lee, Sangjun; Jang, Jieun; Abe, Sarah Krull; Rahman, Shafiur; Saito, Eiko; Islam, Rashedul; Gupta, Prakash C; Sawada, Norie; Tamakoshi, Akiko; Shu, Xiao-Ou; Koh, Woon-Puay; Sadakane, Atsuko; et al.
Abstract: Background: The association between body mass index (BMI) and oesophageal cancer (OC) has been consistently negative among Asians, whereas different associations based on histological OC subtypes have been observed in Europeans and North Americans. We examined the association between BMI and OC mortality in the Asia Cohort Consortium. Methods: We performed a pooled analysis to evaluate the association between BMI and OC mortality among 842 630 Asians from 18 cohort studies. Cox regression models were used to estimate hazard ratios (HRs) and 95% CIs. Results: A wide J-shaped association between BMI and overall OC mortality was observed. The OC mortality risk was increased for underweight (BMI <18.5 kg/m 2 : HR = 2.20, 95% CI 1.80–2.70) and extreme obesity (BMI ≥35 kg/m 2 : HR = 4.38, 95% CI 2.25–8.52) relative to the reference BMI (23–25 kg/m 2 ). This association pattern was confirmed by several alternative analyses based on OC incidence and meta-analysis. A similar wide J-shaped association was observed in oesophageal squamous cell carcinoma (OSCC). Smoking and alcohol synergistically increased the OC mortality risk in underweight participants (HR = 6.96, 95% CI 4.54–10.67) relative to that in reference BMI participants not exposed to smoking and alcohol. Conclusion: Extreme obesity and being underweight were associated with an OC mortality risk among Asians. OC mortality and BMI formed a wide J-shaped association mirrored by OSCC mortality. Although the effect of BMI on OSCC and oesophageal adenocarcinoma mortality can be different in Asians, further research based on a large case–control study is recommended.